1992
DOI: 10.3109/13813459208998113
|View full text |Cite
|
Sign up to set email alerts
|

Regional amines levels in the rat brain following intra-accumbens cholecystokinin and intraperitoneal amphetamine pre-treatment

Abstract: Cholecystokinin octapeptide (CCK8) coexists with dopamine (DA) in a subpopulation of mesolimbic DA neurons including the projections to the nucleus accumbens. In this structure, CCK8 has been reported to exert agonist-like or antagonist-like effects on DA-mediated behaviours and on amphetamine's locomotor-activating effects in rodents. These findings raise the possibility that CCK8 plays a role in modulating the neurochemical mechanisms underlying the effects of DA and amphetamine in the mesolimbic DA system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, it has been consistently demonstrated that CCK inhibits 5HT activity in the brain (Heidbreder et al 1992;Kaneyuki et al 1989;Rex et al 1997;Vasar et al 1985;Widerlöv et al 1983). It is not known whether these effects are mediated by CCK-A receptors.…”
Section: Discussionmentioning
confidence: 96%
“…However, it has been consistently demonstrated that CCK inhibits 5HT activity in the brain (Heidbreder et al 1992;Kaneyuki et al 1989;Rex et al 1997;Vasar et al 1985;Widerlöv et al 1983). It is not known whether these effects are mediated by CCK-A receptors.…”
Section: Discussionmentioning
confidence: 96%
“…Cholecystokinin (CCK) is a neurotransmitter that is very widely distributed throughout the brain, as are its receptors (principally CCK-B type) [154]. CCK interacts with serotonin, dopamine and noradrenaline systems [155][156][157] and in general antagonizes enkephalins. It is co-localized with dopamine in some neurons [158].…”
Section: Possibilities For Specific Pharmacological Therapymentioning
confidence: 99%
“…Specifically, CCK stimulates DA release by acting on CCK-1 receptors [4], while activation of the CCK-2 receptor confers an inhibitory effect on DA release [22]. In contrast to the ubiquitous presence of CCK-2 receptors throughout the brain, populations of central CCK-1 receptors are only known to exist within limited regions, such as the dorsomedial hypothalamus [23,30] and striatum [10], with specifically high intensity in the caudo-medial shell of the nucleus accumbens (NAcc) [17,20]. In the caudal NAcc, DA and CCK are co-released in vivo after administration of drugs that increase DA neuronal firing rate [4,19].…”
Section: Introductionmentioning
confidence: 99%